S-3′-hydroxy-7′, 2′, 4′-trimethoxyisoxane, a novel ferroptosis inducer, promotes NSCLC cell death through inhibiting Nrf2/HO-1 signaling pathway - Chen, Jing; Zhou, Songlin; Zhang, Xian; Zhao, Huange (Frontiers in Pharmacology, 2022)
Background: Ferroptosis is a newly discovered and promising non-apoptotic programmed cell death (PCD), and induction of ferroptosis in cancer cells may open up a novel avenue for drug screening and cancer therapy. S-3'-hydroxy-7', 2', 4’-trimethoxyisoxane (ShtIX), a new isoflavane compound, has been reported to possess cytotoxicity activity in non-small cell lung cancer (NSCLC). The purpose of the study is to explore the ShtIX-induced cell death modality and its underlying molecular mechanism in NSCLC. Methods: The ability of ShtIX to kill NSCLC cells were evaluated by the cell proliferation, cell cycle arrest and cell death assays. Ferroptosis triggered by ShtIX detected by measuring iron metabolism, Fe2+ content, reactive oxygen species (ROS) production, lipid peroxide (MDA) level, glutathione (GSH) and glutathione peroxidase 4 (GPX4) level. We performed western blot, quantitative real-time PCR and Nrf2-siRNA interference in NSCLC cells to investigate the underlying roles of Nrf2/HO-1 in ShtIX-induced ferroptosis. The antitumor effect of ShtIX and the role of ferroptosis investigated in a xenograft nude mouse mode. Results: Our results show that ShtIX can selectively kill NSCLC cells but not normal cells and that ShtIX-induced cell death can be effectively reversed by ferroptosis inhibitors and the iron chelator but not by the other cell death inhibitors. Increased Fe2+ content and lipid peroxidation accumulation after cells were treated with ShtIX, as well as decreased the GSH and GPX4 levels, all of which are the key hallmarks of ferroptosis. Furthermore, ShtIX suppressed the expression of Nrf2 and HO-1, and Nrf2 genetic silencing in NSCLC enhanced the effect of ShtIX-induced ferroptosis. In addition, ShtIX also retard the tumor growth and triggered ferroptosis in the A549 xenograft mode, and the impact of antitumor was weakened by Fer-1. Conclusion: This study provided the evidence that ShtIX induced ferroptosis in NSCLC cells and inhibiting the Nrf2/HO-1 pathway can greatly exacerbate the effect of ShtIX-induced ferroptosis. This study provides a scientific basis for ShtIX as a promising natural candidate ferroptosis inducer for NSCLC therapy.